Ocean acidification impacts spine integrity but not regenerative capacity of spines and tube feet in adult sea urchins - Emerson, Chloe E. (R Soc Open Sci, 2017)
Increasing atmospheric carbon dioxide (CO(2)) has resulted in a change in seawater chemistry and lowering of pH, referred to as ocean acidification. Understanding how different organisms and processes respond to ocean acidification is vital to predict how marine ecosystems will be altered under future scenarios of continued environmental change. Regenerative processes involving biomineralization in marine calcifiers such as sea urchins are predicted to be especially vulnerable. In this study, the effect of ocean acidification on regeneration of external appendages (spines and tube feet) was investigated in the sea urchin Lytechinus variegatus exposed to ambient (546 µatm), intermediate (1027 µatm) and high (1841 µatm) partial pressure of CO(2) (pCO(2)) for eight weeks. The rate of regeneration was maintained in spines and tube feet throughout two periods of amputation and regrowth under conditions of elevated pCO(2). Increased expression of several biomineralization-related genes indicated molecular compensatory mechanisms; however, the structural integrity of both regenerating and homeostatic spines was compromised in high pCO(2) conditions. Indicators of physiological fitness (righting response, growth rate, coelomocyte concentration and composition) were not affected by increasing pCO(2), but compromised spine integrity is likely to have negative consequences for defence capabilities and therefore survival of these ecologically and economically important organisms.